Women's asset ownership: Evidence from Georgia; Mongolia; and Cavite, Philippines - Kaushal Joshi; Hema Swaminathan; Arturo Martinez; Mildred Addawe; Christian Flora Mae Soco (Asian Development Bank (ADB), 2019)
Since the implementation of the Millennium Development Goals, significant global progress has been achieved in promoting gender equality in education and health. However, progress has not been as remarkable in advancing women's rights on asset ownership and control, which is critical for securing gender equity in economic participation and opportunity, and delivering on the Sustainable Development Goals. Part of the problem comes from the lack of standards on collecting sexdisaggregated data on the topic. The Evidence and Data for Gender Equality (EDGE) initiative aims to develop standardized methods and guidelines for collecting sex-disaggregated data on asset ownership. This paper provides rich inputs to the methodological guidelines being developed by the United Nations and development partners by drawing on the key findings from the pilot surveys conducted in Georgia; Mongolia; and Cavite, Philippines. Furthermore, survey results suggest substantive gender gaps in ownership across different types of assets and countries. These variations confirm the importance of understanding the social norms governing gender roles in society and legislation that can facilitate or impede women's asset ownership.
Keywords: C80; J16; Q15; 330; asset ownership; gender equality; gender gaps